REDUCTION OF INTRAOCULAR PRESSURE POST MICRO PULSE TRANSSCLERAL CYCLOPHOTOCOAGULATION IN REFRACTORY GLAUCOMA PATIENTS: Oral Presentation - Observational Study - Resident - Rahayu, Annisa; Gustianty, Elsa; Knoch, Andrew M.H; Rifada, Maula; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesCyclodestructive laser is one of the last resource managements for refractory glaucoma, especiallywith low visual potential. Conventional laser using CW-TSCPC showed unstable IOP reduction withcollateral tissue damage. MP-TSCPC using on and off cyclic waves is considered to have a gooddegree of IOP reduction and fewer complications. The purpose of this study is to assess the IOPreduction after the MP-TSCPC procedures for patients with refractory glaucoma. MethodsThis is a prospective observational study for refractory glaucoma patients treated with the MPTSCPClaser procedure. Measurement of IOP was carried out preoperatively and on postoperativedays 1, 7, and 30 with the gold standard Goldmann applanation tonometry. ResultsA total of 33 eyes from 33 patients were enrolled in this study. The mean baseline IOP was 48.45 ±12,79 mmHg. The mean degree of IOP reduction on follow-up days 1, 7, and 30 were 14.39 ±23.52%, 45,83 ± 24,80 and 27.09 ± 23.86% respectively. On the 30th day after the laser treatment,no complications were observed. The number of anti-glaucoma medication was reduced from 2.39 ±0.49 at the baseline to 1.91 ± 0.58 at one month follow up. ConclusionMicro-pulse transscleral cyclophotocoagulation laser showed a good degree of IOP reduction with noincidence of complication observed at day 30.